Peran Kepemimpinan dalam Pengembangan Mutu Pendidikan Islam - Diky Wahyudi; Cahya Ayu Kamila; Sri Wulandari Agustin (Jurnal Syntax Transformation, 2021)
In the current era, the development of Islamic educational institutions in Indonesia seems to be increasingly complicated. The management model requires a more modern and relevant arrangement to the times in order to be able to compete with other public institutions. Therefore, improving the quality of education is an important issue that requires more attention and handling by the relevant parties. This is closely related to school leadership and management. In addition, to improve the quality of education must pay attention to all aspects of the school, including inputs, processes and outputs. The quality of education is seen as necessary for improvement and transformation in all departments, including the leadership and management departments. School success depends on effective management, and effective management depends on professional leadership. A leader's responsibilities as a manager include planning and evaluation, organising, directing and monitoring, and ongoing monitoring and evaluation for future action.